Survival at 2 years among liver cirrhotic patients is influenced by left atrial volume and left ventricular mass. (19th November 2016) - Merli, Manuela; Torromeo, Concetta; Giusto, Michela; Iacovone, Gianna; Riggio, Oliviero; Puddu, Paolo E.
Abstract: Background & Aims: Cirrhotic cardiomyopathy (CC) may interact with the clinical course of cirrhosis and can be implicated in the development of several complications in advanced liver disease. The best and easiest parameters which should define a condition of reduced cardiac reserve in cirrhosis are still controversial. This study was aimed at selecting the cardiac parameters, derived by Doppler echocardiography, predictive of survival during follow‐up. Methods: This study included cirrhotic patients without cardiovascular or pulmonary diseases. Patients were studied in stable conditions. Doppler echocardiography was used to select parameters associated with survival. Among the others, left atrial volume (LAVi) and left ventricular mass indexed to body surface area (LVMi) were evaluated. A comparison was performed with the parameters presently applied for the definition of CC according to the Montreal criteria. Results: Ninety cirrhotic patients have been included (males 66%, alcohol origin 31%, post‐viral 54%, Child‐Pugh A 53%, B 29% and C 18%). Patients were followed up for at least 24 months. Twenty‐six patients had a diagnosis of CC according to the Montreal criteria. During follow‐up, 24 patients died. Overall mortality was 26.7%. Patients presenting higher LAVi and lower LVMi were those at higher risk to die ( P =.04 and P =.007 respectively). No difference in survival was seen in patients with a diagnosis of CC. Conclusions: An increased LAVi and a decreased LVMi were able to differentiate among patients with a lower survival at 2 years. These parameters need to be considered for prognostic evaluation in cirrhotics.